Concentrations of PCDD/PCDFs in plasma of subjects living in the vicinity of a hazardous waste incinerator: Follow-up and modeling validation - Nadal, Martí; Perelló, Gemma; Schuhmacher, Marta; Cid, Joan; Domingo, José L. (Chemosphere (Oxford), 2008)
In 2007, the concentrations of polychlorinated dibenzo- p-dioxins and dibenzofurans (PCDD/PCDFs) were determined in plasma of non-occupationally exposed subjects living near the only hazardous waste incinerator (HWI) in Spain (Constantí, Tarragona County, Catalonia). These data were compared with the levels found in two previous surveys performed in 1998 (baseline) and 2002. The current mean PCDD/PCDF concentration in plasma was 9.36 pg I-TEQ g −1 of lipid (range: 1.76–23.44 pg I-TEQ g −1 of lipid). It means a significant reduction of the mean PCDD/PCDFs levels in plasma in comparison to the concentrations found in 1998 and 2002 (27.01 and 15.70 pg I-TEQ g −1 of lipid, respectively). This important decrease agrees well with the notable reduction in the dietary intake of PCDD/PCDFs recently noted for the population of the same area (210.1 pg I-TEQ d −1, 63.8 pg WHO-TEQ d −1, and 27.8 pg WHO-TEQ d −1, in 1998, 2002 and 2007, respectively). The current data were also used to predict theoretical PCDD/PCDF concentrations in plasma by executing a single-compartment empirically-based pharmacokinetic model on the basis of the daily intake of these pollutants by the local population.